The interaction of selective plant lectins with neuraminidase-treated and untreated IgA1 from the sera of IgA nephropathy patients - Hashim, Onn Haji; Shuib, A.S.; Chua, C.T. (2001)
A study on the binding interaction of lectins from Artocarpus heterophyllus (jacalin), Glycine max and Sambucus nigra with standardised quantity of IgA from the IgA nephropathy patients and normal controls was performed. The Glycine max lectin demonstrated higher affinity towards the serum IgA of IgAN patients as compared to normal controls. However, the affinity binding was lower in cases of jacalin and the Sambucus nigra lectin. When serum samples were treated with neuraminidase, the differential jacalin affinity binding between IgA1 of patients and normal controls was abrogated. Our data are in support of the view that the O-linked oligosaccharide moieties of the patients IgA1 were generally lacking in galactose and sialic acid residues.